THE RELATIONSHIP BETWEEN EMPATHY AND BULLYING BEHAVIOR IN SMKN STUDENTS IN WEST CIKARANG - Rihya Syifa Qurrotu Ayuna; Karsih Karsih; Herdi Herdi (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to obtain an overview of the level of empathy and its relationship with bullying behavior in students of State Vocational High School (SMKN) in West Cikarang. This study uses a quantitative approach with a correlational method to identify the relationship between empathy variables and bullying behavior. The sampling technique used was convenience sampling, with a total of 124 respondents from SMKN students in West Cikarang. This method was chosen because of the ease of access to research subjects that are in accordance with predetermined criteria. Data collection was carried out using two main instruments, namely the bullying instrument adapted from the Brazilian Portuguese version of the Olweus Bully/Victim Questionnaire (OBVQ) to measure bullying behavior, and the Interpersonal Reactivity Index (IRI) to measure students' empathy levels. Both instruments have been widely used in previous studies and have good validity and reliability in measuring the construct in question. The data analysis techniques used in this study are descriptive statistics and correlation analysis to see the relationship between the two variables. The results of the study showed that there was a significant negative relationship between empathy and bullying behavior in SMKN students in West Cikarang. This means that the higher the level of empathy that students have, the lower their tendency to engage in bullying behavior. Conversely, low empathy is associated with increased potential for bullying behavior. These findings affirm the importance of developing empathy as one of the preventive efforts to reduce bullying behavior in the school environment, as well as being the basis for schools to design more effective and sustainable intervention programs.